Superior electromagnetic interference shielding performances of epoxy composites by introducing highly aligned reduced graphene oxide films. (September 2019) - Liang, Chaobo; Song, Ping; Qiu, Hua; Huangfu, Yiming; Lu, Yuanjin; Wang, Lei; Kong, Jie; Gu, Junwei
Abstract: Reduced graphene oxide films (RGFs) were fabricated by the method of bar-coating followed by chemical and thermal reduction. And the RGFs/epoxy resin (RGFs/EP) electromagnetic interference (EMI) shielding composites were prepared by introducing RGFs into EP matrix via pre-arrangement method. The introduction of highly aligned RGFs with layered structure was more conducive to improving the EMI shielding effectiveness (SE) and in-plane electrical conductivities of the RGFs/EP EMI shielding composites. A superior EMI SE value of 82 dB was achieved for 8-RGFs/EP EMI shielding composites at X-band, almost 41 times higher than that of pure EP (∼2 dB). Superior EMI shielding performances are mainly attributed to multiple reflection, absorption and scattering inside and between RGFs interlayers, and the shielding mechanism is mainly ascribed to absorption. Meantime, the obtained in-plane electrical conductivitiy significantly increases from 10 −12  S/m of pure EP to 591.7 S/m of the 8-RGFs/EP EMI shielding composites.